PELAKSANAAN PEMBIMBING KEMASYARAKATAN DALAM SISTEM PERADILAN PIDANA ANAK DI BALAI PEMASYARAKATAN KELAS I PADANG - Matisa, Sairah; Deliana, Evi; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Issues regarding child development are important, children in difficult situations can act against the law. It shows by some child criminal cases at the Padang Class I Correctional Center in 2018. It makes the role of Community Guidance in the Juvenile Criminal Justice System indispensable. This study aims to describe the implementation of Community Guidance in the Juvenile Criminal Justice System along with the obstacles and efforts made by the Correctional Center for children who do not get full Community Guidance assistance.The research used sociological legal research by taking population and sample from parties that related to the problem under study, they are the Community Advisors at the Class I Correctional Center in Padang City and children who were dealing with the law. This research is guided by Undang-Undang Nomor 11 Tahun 2012 concerning the Juvenile Criminal Justice System. The Correctional Center (Balai Pemasyakarakatan or BAPAS in Indonesia) has an important role in protecting children in conflict with the law, inside and outside the criminal justice process.The results of this study conclude that the implementation of Community Guidance in the Juvenile Criminal Justice System is mentoring activities still not running by applicable regulations, this can be seen from the existence of some Community Advisory mentoring processes that cannot attend caused by several obstacles. The factors that inhibit children from not getting fully assistance, among others lack of socialization by the correctional center, large work area, small community guidance, less financial budget and limited service vehicles. This study also found that children's knowledge about the role of Correctional Facilities and Community Guidance is very minimal.Keywords: Implementation - Community Guidance - Correctional Center - Children